Dilema Pelaksanaan Urusan Pemerintahan Umum di Kecamatan oleh Camat (Studi di Kecamatan Kahayan Tengah Kabupaten Pulang Pisau) - John Retei Alfri Sandi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
The affairs of public government have an important urgency amid diversity, the threat of intolerance, radicalism, the disintegration of the nation today. The central institutional role in the region is both security and order-based, defense will be difficult to run optimally without the support of the organizational structure of regional devices with its work program. Regulatory, technical and political constraints will be officials in the allocation of work programs and regional budgets to leading organizational units such as the sub-district government being the cause of the lack of public government affairs properly maintained by the District Court in the sub-district. This research seeks to examine the dilemma of conducting public government affairs in The Central Kahayan District of Pulang Pisau Regency by the district, amid current reforms and democracy that gives broad authority to districts/ cities as well as village governments with village laws and budgets of one billion villages through a qualitative scripted approach.